Prototype Mesin Presensi Berbasis E-mail Pada SMP Assyairiyah Attahiriyah Jakarta - Sunandar Sunandar; Herlawati Herlawati (Journal of Students‘ Research in Computer Science, 2020)
This research discusses the design of E-mail-based Presence Machine Prototype in Assyairiyah Attahiriyah Junior High School Jakarta which aims to information for parents and schools who have difficulty monitoring student attendance at school, thus helping to manage student presence data more effectively and efficiently. The system development method used is the Prototype method. Data obtained by conducting interviews and direct observation of spaciousness to get right data as needed. The results of this research are hardware and software, in the process of making hardware using NodeMCU, LCD 16x2, Buzzer and Fingerprint Sensor and the software uses the PHP programming language with MySql database. The presence of the Presence Machine Prototype becomes a means for parents and schools to process and get information related to student attendance in schools effectively and efficiently. Keywords: Presence Machine, Presence, Prototype, NodeMCU. Abstrak Penelitian ini membahas perancangan Prototype Mesin Presensi Berbasis E-mail yang bertujuan sebagai sarana informasi bagi orang tua maupun pihak sekolah yang kesulitan memonitoring kehadiran siswa disekolah, sehingga membantu pengelolaan data presensi siswa menjadi lebih efektif dan efisien. Metode pengembangan sistem yang digunakan adalah metode prototype. Data diperoleh dengan melakukan wawancara serta observasi langsung kelapangan guna mendapat data yang akurat sesuai yang dibutuhkan. Hasil penelitian ini berupa hardware dan software, dalam proses pembuatan hardware menggunakan NodeMCU, LCD 16x2, Buzzer dan Sensor Fingerprint serta softwarenya menggunakan bahasa pemrograman PHP dengan database MySql. Adanya Prototype Mesin Presensi ini menjadi sarana bagi orang tua dan sekolah untuk mengolah dan mendapatkan informasi terkait presensi siswa disekolah dengan efektif dan efisien. Kata Kunci: Mesin Presensi, Presensi, Prototype, NodeMCU.